The Oxford handbook of management ideas - Sturdy, Andrew,; Heusinkveld, Stefan,; Reay, Trish,; Strang, David, (Oxford handbooks online., 2019)
Management ideas, and their associated applications, have become a prevalent feature of our working lives. While their focus is familiar, such as efficiency, motivation, and improvement, they range from specific notions such as activity-based costing, to broad movements like corporate social responsibility. Providing an up to date, enduring, and authoritative account of the field of research on management ideas, this work addresses questions of where management ideas come from, how they are produced, promoted and used, and their effect on business and working practices.